Kualitas Pelayanan Pasien Badan Penyelenggara Jaminan Sosial Rawat Jalan di Poliklinik Rumah Sakit Umum Madani Provinsi Sulawesi Tengah - Yusnitha; Mohamad Irfan Mufti; Nasrullah (Jurnal Administrasi Pemerintahan Desa, 2026)
The research method used was qualitative with a descriptive type. Data collection techniques consisted of observation, interviews, and documentation. Data analysis used an interactive model and SWOT analysis. The results of the study, namely the Madani Regional General Hospital (RSUD) according to the five SERVQUAL Aspects namely tangibles, reliability, responsiveness, assurance, and empathy, have been implemented in the services of Madani Regional General Hospital with varying levels. The reliability and assurance aspects are the most prominent aspects, because medical personnel have provided services in accordance with SOPs, upholding professionalism, and creating a sense of security and trust for patients. The empathy aspect is also seen strongly through the friendly attitude, patience, and willingness of medical personnel to listen to patient complaints. Meanwhile, tangibles and responsiveness still need improvement, especially in the completeness of facilities and efficiency of service time. showing quite good performance, although there are still some aspects that need to be improved. In addition, the Madani Regional General Hospital (RSUD) has been able to balance between technical aspects and humanistic aspects in services, by maintaining the competence of medical personnel while paying attention to the emotional needs of patients.